Relation between perceived social support and health promotion behaviors in chemical veterans in Ilam province on 2012-13 - R. Chenary; A. Noroozi; R. Noroozi (Afarand Scholarly Publishing Institute, 2014)
Background & Purpose: Chemical attacks in war can make short term and long term personal, family and social damages and limited social relationships of victims as compared to ordinary people. The aim of this study was to investigate the relationship between social support and health promoting behaviors in chemical veteran in Ilam province 2012-13. Methods & Materials: This cross-sectional study was performed in the entire moderate and severs chemical veterans, who they were covered by the Department of Veterans and Martyrs of Ilam province. Information was collected by using standard questionnaires for health-promoting behavior and Multidimensional scale of perceived social support (family, friends, and important people). The reliability and validity of these instruments was desirable. Inclusion criteria were percentage of disability with moderate and sever levels and enough physical strength to answer questions, and exclusion criteria were also lack of cooperation and have no permanent residence in Ilam province. After data collection, all data were analyzed by SPSS statistical soft ware and Pearson correlation coefficient and linear regression. Results: All of 239 veterans indicated that all of them were men with mean and standard deviation age 51.17± 8.87 years and there is a significant relation between all subscales of social support and health-promotion behavior subscales (p<0.05). Among the subscales of social support, friend support had the highest correlation with health-promoting behaviors (r= 0.391), and support from important people showed the lowest correlation (r= 0.367). The all regression models of health promotion behavior and its subscales were significant. Conclusion: There is a relation between perceived social support especially friend support and health-promotion behaviors, therefore suggest that the friend as a resource support was used in design of educational programs.